An investigation into virtual objects learning by using haptic interface for visually impaired children - Chit, Su Mon *; Yap, Kian Meng * (Sunway University, 2012)
Children play, touch, see and listen in order to build the foundation for later learning stage of solving problems and understanding themselves within the world surrounding them. However, visually impaired children have limited opportunities in learning new things compared to normal sighted children who have one of the important senses of a human being. Children gain knowledge through learning, playing, touching, seeing, listening and interacting with things that they are interested in. For visually impaired children, learning is different from normal sighted children in that they cannot go out and play with things without guidance and they are not able to see the picture or video of the things or objects like normal children are. A computer simulated virtual reality environment can provide better opportunities for visually impaired children especially in learning the shapes of new objects. An application utilizing the force feedback technology, i.e. Haptic technology, together with the aid of audio has been developed in this research project. Seven different objects are modelled to create haptic shapes for this application which allows visually impaired users to have a better learning environment and assists them in learning the shapes of different objects and also memorizing the shapes of different objects together with the name. The created application is deployed in a fully equipped computer with a stylus based haptic device and a set of speakers. The new architecture can provide an alternative learning environment for visually impaired children especially in learning the shapes of new objects. Based on the findings of this research, as 79% of the users agreed that virtual reality learning is useful in learning the shapes of new objects, the new architecture creates a significant contribution in a novel research area and assists visually impaired children in continuing their learning process.